FEATURES OF ORTHODONTIC TREATMENT USING LINGUAL BRACES - F.A. BILALOVA; V.I. BONDARENKO; E.M. BASIN; M.YU. KUZNETSOVA (Avicenna Tajik State Medical University, 2021)
Malocclusion and imperfect placement of teeth can have a big impact on the smile, well-being and quality of life. As a result of the treatment of pathological and abnormal bite, many children and adults are forced to use braces to improve their bite. The consequences of treatment are different: inflammation and itching, edema of the oral mucosa and maxillary sinuses, headaches, fever. All this depends on the human physiological characteristics, as well as adaptation to this artificial structure, which actually shifts the teeth from a pathological position to a physiological one. Correcting the bite with lingual braces has a key advantage. The main thing is the ability to cope with the psychological barrier that inevitably arises when wearing vestibular braces. But there is also a disadvantage that manifests itself in a short-term speech disorder for 2-3 months. This article discusses the procedure for making lingual braces, the stages and principles of installing lingual braces, recommendations for the care and wearing of the structure, as well as the impact of these braces on the speech apparatus and articulation of speech sounds and the possible development of logoneurosis due to treatment with lingual braces.